Clinicopathologic study of Kikuchi’s disease in children in a tertiary hospital in South India - Punnen, Anu; ., Kanagalakshmi; Manipadam, Marie Therese; Verghese, Valsan Philip; Mathew, Leni Grace; Kumar, Sathish (International Journal of Contemporary Pediatrics, 2019)
Background: The aim of this study was to evaluate the clinical and laboratory characteristics, treatment modalities and outcome of children with Kikuchi’s disease. Methods: A retrospective cross-sectional study was conducted among all children, histopathologically diagnosed with KFD. Clinical, laboratory data and treatment outcomes were analysed. Results: During the study period, 53 children histopathologically confirmed as KFD were enrolled in the study. There were 36 males and 17 females. The lymph node involvements were mostly cervical with bilateral predisposition (63.5%), firm (88%), matted (30.8%) and tenderness (38.5%). Fever, headache, vomiting, chills, myalgia and rash were other common presentations other than cervical lymphadenopathy. The associated laboratory findings include anemia (71.2%), leukopenia especially lymphopenia (31.4%), monocytosis (21.6%), thrombocytopenia (16.3%), elevated CRP (53.1%), ESR (83.7%), LDH (100%) and elevated liver enzymes. Most of the children were managed conservatively (49.1%). Corticosteroids were administered for (22.6 %) of patients. Recurrence occurred in 4 children (7.5 %) and 13 children (24.5%) had other associated diseases. Conclusions: KFD should be suspected in well children with febrile cervical lymphadenopathy, especially with leukopenia, monocytosis, and elevated CRP, ESR, LDH, Liver enzymes. KFD in children can have rarely atypical presentations and coexist with other diseases.